2003
DOI: 10.1007/s11663-003-0052-7
|View full text |Cite
|
Sign up to set email alerts
|

Laminar-turbulent transition in an electromagnetically levitated droplet

Abstract: During experiments on the MSL-1 (first microgravity science laboratory) mission of the space shuttle (STS-83 and STS-94, April and July 1997), a droplet of palladium-silicon alloy was electromagnetically levitated for viscosity measurements. For the nondeforming droplet, the resultant magnetohydrodynamic (MHD) flow inside the drop can be inferred from motion of impurity particulates on the surface. In the experiments, subsequent to melting, Joule heating produces a continuous reduction of viscosity of the flui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 24 publications
5
45
0
Order By: Relevance
“…A transition from a laminar to a turbulent flow regime as a function of the rf-heater field could be demonstrated. In related experiments Egry [25] et al and Hayers [26] et al could demonstrate that under laminar flow conditions realistic viscosity values in agreement with independently measured values could be obtained. Thus, it can be safely assumed that with the heater field turned off, the positioner field reduced, and with the time delay between the shut off of the heater field and the application of pulses for surface oscillation excitation, turbulent fluid flow is absent providing realistic values of the viscosity.…”
Section: Viscositysupporting
confidence: 64%
“…A transition from a laminar to a turbulent flow regime as a function of the rf-heater field could be demonstrated. In related experiments Egry [25] et al and Hayers [26] et al could demonstrate that under laminar flow conditions realistic viscosity values in agreement with independently measured values could be obtained. Thus, it can be safely assumed that with the heater field turned off, the positioner field reduced, and with the time delay between the shut off of the heater field and the application of pulses for surface oscillation excitation, turbulent fluid flow is absent providing realistic values of the viscosity.…”
Section: Viscositysupporting
confidence: 64%
“…Berry et al 17) showed that the localized viscosity can change by a factor of 2 due to positioning field while the heating coils can alter by a factor of four causing considerable anisotropic distribution of flow. Hyers et al 18) later showed that flow inside the droplet can change from a laminar flow to viscous flow as the Reynold's number reaches 600 (this value is about 2 300 for water flowing in a pipe) and used tracers to demonstrate that "noncoherent chaotic motion signifying emergence of turbulence inside the drop" occurs due to EML. Since viscosity controls Reynold number to a considerable extent and since it was shown that the viscosity is nonuniform within the droplet, the flow also could be complex having laminar to turbulent characteristics within the droplet.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the levitation field also induces fluid flow in the melt. 16) Therefore containerless techniques are only applicable to those problems where absence of convection is not mandatory. Thermophysical properties of levitated samples have been measured in microgravity during two Spacelab missions, using the electromagnetic levitation facility TEMPUS.…”
Section: Containerless Methodsmentioning
confidence: 99%